WECHSLER ADULT INTELLIGENCE SCALE - Nazira Dyah Maharani; Nur Azizah Maulidyah A.R; Nurul Azizah Maghfiroh; Nur Eva (Flourishing Journal, 2022)
Abstract: Measurement of psychological attributes in the form of intelligence or personality is still the most important thing in psychological tests. One of the initial problems that underlie the development of psychological tests is how to identify people who are mentally retarded. Psychological test tools can not be separated from its function which is to measure the psychological condition of the individual. The emergence of intelligence test tools, one of which is the Wechsler Adult Intelligence Scale (WAIS) which is used to obtain IQ for adolescents who have above average functions and also determine cognitive function for adults. The method used by the author in this article is a literature study used to find data Keywords: WAIS; Weschler; Intelligence; Adult. Abstrak: Pengukuran atribut psikologis berupa intelegensi atau kepribadian masih menjadi hal yang paling utama dalam tes psikologi. Salah satu masalah awal yang mendasari tumbuhnya tes-tes psikologi adalah bagaimana cara mengidentifikasi orang yang mengalami keterbelakangan mental. Alat tes psikologi tidak lepas dari fungsinya yang dimana untuk mengukur kondisi psikologis dari individu. Munculnya alat tes intelegensi yang salah satunya adalah Wechsler Adult Intelligence Scale (WAIS) yang digunakan digunakan untuk memperoleh IQ bagi remaja yang memiliki fungsi di atas rata-rata dan juga menentukan fungsi kognitif bagi orang dewasa. Metode yang digunakan oleh penulis di dalam artikel ini merupakan studi literatur yang digunakan untuk mencari data Kata kunci WAIS; Weschler; Intelegensi; Dewasa